PENGARUH LIKUIDITAS, STRUKTUR MODAL, STRUKTUR KEPEMILIKAN, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN PERUSAHAAN INDEKS LQ45 PERIODE 2017-2022 - Furqoni, Muhammad Iqbal; Anggraeni, Anggraeni (LPPM Institut Pendidikan Nusantara Global, 2023)
The purpose of this study was to determine the effect of cash ratio, debt to equity ratio, institutional ownership, managerial ownership, and company size on the dividend payout ratio. The sample for this study were 8 companies listed on the LQ45 index on the Indonesia Stock Exchange for 2017-2022, which were selected through a purposive sampling method. The results of this study using multiple linear regression analysis show that firm size partially has a significant negative effect on the dividend payout ratio, while the cash ratio, debt to equity ratio, institutional ownership, and managerial ownership partially have no significant effect on the dividend payout ratio.